2016
DOI: 10.14309/crj.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

Rare Jejunal Diverticular Bleeding

Abstract: Severe gastrointestinal bleeding (GIB) secondary to jejunal diverticulosis (JD) is very rare. Delay in establishing a diagnosis is common and GIB from JD is associated with significant morbidity and mortality. We report an illustrative case diagnosed by push enteroscopy and managed with surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…2 Jejunal diverticulum was first illustrated in 1794 by Somerling and revisited in 1807 by Sir Astley Cooper. 3 Diverticula in proximal jejunum tend to be larger and multiple in numbers than other parts of intestine, similar to the one described in this case. Majority of jejunal diverticulum is asymptomatic, but 10-30% presented with intestinal haemorrhage, small bowel perforation, diverticulitis, abscess, intestinal obstruction and malabsorption.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…2 Jejunal diverticulum was first illustrated in 1794 by Somerling and revisited in 1807 by Sir Astley Cooper. 3 Diverticula in proximal jejunum tend to be larger and multiple in numbers than other parts of intestine, similar to the one described in this case. Majority of jejunal diverticulum is asymptomatic, but 10-30% presented with intestinal haemorrhage, small bowel perforation, diverticulitis, abscess, intestinal obstruction and malabsorption.…”
supporting
confidence: 80%
“…The true incidence of jejunal diverticulum remains unknown, but autopsy studies reported an estimated incidence of 0.4–4.0% 2 . Jejunal diverticulum was first illustrated in 1794 by Somerling and revisited in 1807 by Sir Astley Cooper 3 . Diverticula in proximal jejunum tend to be larger and multiple in numbers than other parts of intestine, similar to the one described in this case.…”
Section: Figuresupporting
confidence: 63%
“…es are caused by diverticula of the small intestine, corresponding to approximately 50 documented cases in the literature [2]. The CE diagnostic accuracy is higher when performed within 2 weeks after the bleeding episode (91% vs. 34%), which has also been shown for double-balloon enteroscopy [3].…”
Section: Discussionmentioning
confidence: 87%
“…Therapeutic modalities include clipping, argon plasma coagulation, or band ligation [2]. As there are only a few case reports in the literature, the short-and long-term efficacy of endoscopic therapy is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…GI bleeding from jejunal diverticulosis, first reported by a British surgeon, Dr L.R. Braithwaite in 1923, has a reported incidence of approximately 3.4%-8.1%, although severe GI bleeding secondary to jejunal diverticulosis is rare, with 1 study quoting approximately 50 cases reported in the literature to date [19] . Hemorrhage can be due to ulceration or foreign body impaction [5] .…”
Section: Discussionmentioning
confidence: 99%